Comparative Analysis of the Fecal Bacterial Microbiota of Wintering Whooper Swans (Cygnus Cygnus) - Wang, Wenxia; Huang, Songlin; Yang, Liangliang; Zhang, Guogang (Frontiers in Veterinary Science, 2021)
There are many and diverse intestinal microbiota, and they are closely related to various physiological functions of the body. They directly participate in the host's food digestion, nutrient absorption, energy metabolism, immune response and many other physiological activities, and are also related to the occurrence of many diseases. The intestinal microbiota is extremely important for maintaining normal physical health. In order to explore the composition and differences of the intestinal microbiota of whooper swans in different wintering areas, we collected fecal samples of whooper swans in Sanmenxia, Henan and Rongcheng, Shandong, and used the Illumina Hiseq platform to perform high-throughput sequencing of bacterial 16S rRNA genes. Comparison between Sanmenxia and Rongcheng showed no significant differences in Ace，Chao 1，Simpson，Shannon indices (P > 0.05). Beta diversity results showed significant differences in bacterial communities between two groups (ANOSIM: R = 0.80, P = 0.011). Lefse analysis showed that at the phylum level, the relative abundance of Actinobacteria was significantly higher in Sanmenxia whooper swans than Rongcheng whooper swans. At the genus level, the amount of Psychrobacter and Carnobacterium in Sanmenxia were significantly higher in Rongcheng. While the relative abundance Catellicoccus and Lactobacillus were significantly higher in Rongcheng than in Sanmenxia. This study analyzed the composition, characteristics, and differences of the intestinal microbiota of the whooper swans in different wintering environments, and provided theoretical support for further exploring the relationship between the intestinal microbiota of the whooper swans and the external environment. And it played an important role in the overwintering physiology and ecology, population management and epidemic prevention and control of whooper swans.